IFRS CONVERGENCE AND INTERNATIONAL TRADE: EVIDENCE FROM COMPARISON OF TÜRKIYE AND EUROPEAN UNION - Çatuk, Cüneyt; Uygur, Mehmet Nedim (Vilnius Gediminas Technical University, 2025)
The congruence of accounting standards with high-quality financial data constitutes a cornerstone of the institutional frameworks of modern economies. The adoption of International Financial Reporting Standards (IFRS) facilitates greater transparency and comparability in financial reporting, enabling more ef fective allocation of resources and capital. This process enhances the stability of financial systems, improves corporate governance, and supports integration into global economic framework. This study seeks to address the following research questions: (1) How does the adoption of IFRS by Turkey influence its trade flows with the EU? (2) How do income disparities between Türkiye and EU member states interact with IFRS adoption to affect bilateral trade? (3) What is the macroeconomic importance of IFRS adoption to Türkiye’s overall trade balance? Through answering these questions, this research intends to contribute to filling an important gap in literature. The results of this research; First, IFRS adoption by Turkey reflects an immense positive impact both on exports and imports, with exports bearing more impact. This research draws attention to IFRS adoption’s role in promoting financial transparency, optimizing bilateral flows, and minimizing trade deficit in Turkey. Second, how IFRS adoption interacts with disparities in per capita income tells us more about trade behavior. Third, macroeconomic consequences of IFRS adoption are reflected in how IFRS adoption decreases Turkey’s trade deficit. The results indicate that IFRS adoption encourages exports more than imports, which points to IFRS adoption acting as an instrument to raise competitiveness and overall Turkish trade balance. This find ing answers the third research question, which draws attention to how instrumental IFRS adoption is to frame trade policy and economic integration. © 2025 The Author(s).
Keywords: cost accounting; exports; imports; institutional frameworks; international financial reporting standards; trade dynamics; Türkiye and EU member